Translation, Heterogeneity, Linguistics - Venuti, Lawrence (TTR)

(untitled) (Association canadienne de traductologie, 1996)
AbstractTranslation, Heterogeneity, Linguistics — As an American translator of literary texts I devise and execute my projects with a distinctive set of theoretical assumptions about language and textuality, assumptions that highlight the power relations in any cultural situation and that therefore carry ethical and political implications for translation. Yet these assumptions, derived from recent European developments in literary and cultural theory (notably poststructuralism and postmarxist sociology), run counter to the linguistics-oriented approaches that currently dominate translation research and translator training, and that tend to construe language, textuality, and hence translation as relatively value-free means of communication. My article describes my conception of translation, considers how it has informed my recent translation projects — both the selection of foreign texts and the development of discursive strategies — and then examines its differences to linguistics-oriented approaches that are based on pragmatics and text linguistics. My aim is not to suggest that such approaches be abandoned, but rather that they be reconsidered from a different theoretical and practical orientation — one that will in turn be forced to rethink itself.